西太平洋MD05-2922岩芯18萬年以來有孔蟲碳氧同位素記錄 - 劉峰榮 (2019)
本研究針對安通爪哇海底高原(Ontong Java Plateau)頂部MD05-2922岩芯(4°59.28 S；156°08.80 E；水深1460公尺)進行底棲性有孔蟲Cibicidoides wuellerstorfi穩定同位素分析，並對比Lisiecki and Raymo (2005)所提出之LR04標準曲線，建立了西赤道太平洋暖池中心18萬年以來的氧同位素年代地層架構。 經由本岩芯與象徵南極中層水(Antarctic Intermediate Water, AAIW)源區的MD97-2120岩芯的C. wuellerstorfi碳同位素相比，結果顯示兩者碳同位素值於冰期較為接近，表示西太平洋地區冰期時受AAIW影響較強，但過去研究認為冰期屬於AAIW生成較弱的時期，因此推估造成西太平洋於冰期時受AAIW影響增強的原因，可能為太平洋其他水團同時在冰期減弱，且減弱幅度較AAIW大，使得水體訊號得以傳送至西太平洋地區。 從印度-太平洋、南大西洋及亞南極區的岩芯記錄觀察，早冰消期普遍存在浮游性有孔蟲碳同位素極小值的現象，其中東太平洋湧升流區的極小值記錄，被認為是AAIW增強的訊號，而西太平洋則被認為沒有明顯的碳同位素極小值記錄出現，但由本岩芯表水及溫躍層種浮游有孔蟲Globigerinoides sacculifer與Pulleniatina obliquiloculata之碳同位素數值發現，西太平洋地區於冰消期亦存在碳同位素極小值事件，而成因主要則是受營養鹽突然增高或海水面上升，有機物大量進入海洋系統，造成海水的碳同位素數值急遽下降的可能性較大。 We have generated both benthic and planktonic foraminiferal oxygen and carbon isotope records of IMAGES (International Marine Past Global Changes Studies) core MD05-2922 from Ontong Java Plateau (4°59.28 S, 156°08.80 E, 263cm long, water depth 1460m). Based on the 18O records of benthic foraminifera Cibicidoides wuellerstorfi, an age model is established for the past 180 ka. The circulation of Antarctic Intermediate Water is thought to make an important contribution to the global ocean–climate system, but the details of this interaction are not fully understood especially in western Pacific. Difference in 13C values between core MD05-2922 and core MD97-2120 (near the source region) during glacial times were less than those during interglacial times indicating that the influence of AAIW increased during glacial times. However, it may not be due to the strengthened of AAIW but due to the weakened of other water masses in this region. The carbon isotope minimum event at the beginning of glacial terminations is a common feature record in planktonic foraminiferal carbon isotopic records. The 13C minimum records in eastern equatorial pacific were thought due to the enhancement of formation of Antarctic Intermediate Water. Our carbon isotopic data of G. sacculifer and P. obliquiloculata appeared the same patterns during deglacial period. ...